REMOTE CLASSROOM A Mobile Learning Platform for Education in Emergencies - Albertsson, Carl; Aringskog, Axel; Arvidsson, Nils; Astorsson, Billy; Cano, Ajla; Wikström, Matilda (My University, 2017)
The aim of this thesis is to investigate and identify the essential design characteristics of an education platform meant to be used for education in emergencies. A sense of safety and normality, better preparation for rebuilding the society, and belief in the future are all aspects that can be derived from education during emergencies. In present day, 3.5 million children are denied education even though it is a human right. This thesis primarily focuses on the area in and around Zaatari refugee camp, located in Jordan close to the Syrian border. The work was conducted as a case study to investigate and get an understanding of the situation where several interviews were held. The case study led to a series of design iterations where concepts where created and evaluated. The iterations concluded into a prototype implemented as a hybrid mobile application. The prototype was evaluated using remote expert sessions and a eld study at Studium, a Swedish for Immigrants center. From the study, it was clear that the situation for refugees di ered both on an individual and geographical level. Although, some general similarities were found that could be applied to most refugees. In the report, these similarities are presented as four core factors; smartphone ownership, economical limitations, weak infrastructure and cultural differences. From these factors, several design characteristics, such as cross-platforming, backward compatibility, short lessons, assessment of understanding, offline usage and sharing, universal design, etc., were identified. Some of these were implemented in the application while some were held on a conceptual level, resulting in an educational platform adapted for refugee needs.
Keywords: Data- och informationsvetenskap; Computer and Information Science